2021
DOI: 10.1177/15248399211008238
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Inequities in Adverse Childhood Experiences and Selected Health-Related Behaviors and Problems Among Maryland Adolescents

Abstract: We examined racial/ethnic inequities in the prevalence of adverse childhood experiences (ACEs) and examined the association between ACEs and selected health-related behaviors and problems. Data for this cross-sectional study come from the 2018 Maryland Youth Risk Behavior Survey/Youth Tobacco Survey, a statewide survey of high school students (n = 40,188). ACEs included caregiver verbal abuse and household food insecurity, substance use or gambling, mental illness, and involvement with the criminal justice sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 9 publications
(12 reference statements)
0
22
0
Order By: Relevance
“…In childhood and adolescence, ELS is not only associated with the heightened risk of adverse health problems [26][27][28][29][30][31][32], including physical illnesses such as headache [33] and asthma [34] but also mental illnesses such as depression, non-suicidal self-injury (NSSI) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A meta-analysis that examined the association between ELS and depression in adolescents found that the association between childhood abuse/neglect and depression was much stronger in adolescents than in adults [50].…”
Section: Introductionmentioning
confidence: 99%
“…In childhood and adolescence, ELS is not only associated with the heightened risk of adverse health problems [26][27][28][29][30][31][32], including physical illnesses such as headache [33] and asthma [34] but also mental illnesses such as depression, non-suicidal self-injury (NSSI) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A meta-analysis that examined the association between ELS and depression in adolescents found that the association between childhood abuse/neglect and depression was much stronger in adolescents than in adults [50].…”
Section: Introductionmentioning
confidence: 99%
“…Past researchers using data from the YRBS have reported that suicidality in high school students is associated with female sex ( 2 , 4 ), sexual minority status ( 47 49 ), adverse childhood experiences ( 50 , 51 ), physical teen dating violence ( 52 ), forced sexual intercourse ( 18 , 53 ), body weight perceptions [both overweight ( 54 , 55 ) and underweight ( 55 )], illicit drug use ( 13 , 18 ), prescription opioid misuse ( 56 58 ) [especially in girls ( 59 )], alcohol use ( 15 , 18 , 60 , 61 ), marijuana use ( 13 , 15 , 62 ), bullying ( 18 , 55 , 63 , 64 ) and cyberbullying ( 18 , 55 , 63 65 ), frequent physical fighting ( 66 ), excessive television/video game/internet use ( 67 , 68 ), insufficient sleep ( 69 ), and even soft drink consumption ( 70 ). With so many variables being associated with suicidality in youth—especially given the very large national sample allowing the identification of statistically significant findings with small effect sizes—it is not particularly surprising that concussion was also associated in the present study, in univariate analyses, and in prior studies using the 2013 ( 45 ) and 2017 YRBS ( 41 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ACEs are inequitably distributed by race and ethnicity, demanding clinicians to embrace the practice of cultural humility 47. Cultural humility turns the lenses of race, culture, and gender upon self rather than other, inviting a stance of curiosity and self-awareness, rather than judgment stemming from implicit bias 48.…”
Section: Methodsmentioning
confidence: 99%
“…Cultural, Historical, and Gender Issues Finally, ACEs are inequitably distributed by race and ethnicity, demanding clinicians to embrace the practice of cultural humility. 47 Cultural humility turns the lenses of race, culture, and gender upon self rather than other, inviting a stance of curiosity and self-awareness, rather than judgment stemming from implicit bias. 48 Culture and gender also influence TIC needs; WOC nurses should ask patients about gender identification, cultural preferences, and practices.…”
Section: Collaboration and Mutualitymentioning
confidence: 99%